МЕКТЕПКЕ ШЕКЕМГИ ЖАСТАҒЫ БАЛАЛАРДЫ КӨРКЕМ-ӨНЕР ДӨРЕТПЕЛЕРИ МЫСАЛЫНДА ЭСТЕТИКАЛЫҚ ТӘРБИЯЛАУ - Уразимова, Т.В. (FAN va JAMIYAT, 2019)
The article is dedicated to the issues of aesthetic, spiritual-creative education of children of the preschool age. Since attention increased in modern society to the problem of the shaping all-round developed, spiritually rich and creative personality, the personality, his spiritual and moral look are formed, first of all, in the process of the education.